Crosstalk between Insulin/IGF-1 and GPCR Signaling Systems: A Novel Target for the Anti-diabetic Drug Metformin in Pancreatic Cancer - Rozengurt, Enrique (2010)
Insulin/insulin-like growth factor 1(IGF-1) receptors and G protein-coupled receptors (GPCR) signaling systems are implicated in autocrine/paracrine stimulation of a variety of malignancies, including ductal adenocarcinoma of the pancreas, one of the most lethal human diseases. Novel targets for pancreatic cancer therapy are urgently needed. We identified a crosstalk between insulin/IGF-1 receptors and GPCR signaling systems in pancreatic cancer cells, leading to enhanced signaling, DNA synthesis and proliferation. Crosstalk between these signaling systems depends on mTOR complex 1 (mTORC1). Metformin, the most widely used drug in the treatment of type-2 diabetes, activates AMP kinase (AMPK), which negatively regulates mTORC1. Recent results show that metformin-induced activation of AMPK disrupts crosstalk between insulin/IGF-1 receptor and GPCR signaling in pancreatic cancer cells and inhibits the growth of these cells in xenograft models. Given that insulin/IGF-1 and GPCRs are implicated in other malignancies, a similar crosstalk mechanism may be operative in other cancer cell types. Recent epidemiological studies linked administration of metformin with a reduced risk of pancreatic, breast and prostate cancer in diabetic patients. We posit that crosstalk between insulin/IGF-1 receptor and GPCR signaling is a mechanism for promoting the development of certain types of cancer and a target for the prevention and therapy of these diseases via metformin administration.